Mwalimu the influence of Nyerere - Legum,Colin (Trenton Africa World Press, 1995)
International Figures such as Father Huddleston and Sir Shridath Ramphal join with Tanzanian scholars to asses, not without criticism, the influential contribution of Julius Nyerere both within his own country and across the Third World. Part One provides an overview of the man and his thought. Part Two focuses on those areas of policy in which Nyerere took a particular interest. Part Three concentrates on the major social, economic and political issues that have been central to the unique Tanzanian experience-unique because of the exceptional man who shaped the first quarter of a century of independence.
Index
Keywords: Development